Pengaruh Efektivitas dan Efesiensi Kerja Terhadap Kinerja Ditpamobvit Polisi Daerah Sulawesi Barat - Mu’fidatul Nurul Hajjad (SEIKO : Journal of Management & Business, 2022)
This study aims to determine the effect of the variable Effectiveness Work And Efficiency Work To Performance of DITPAMOBVIT West Sulawesi Regional Police. The research method used is by using quantitative methods with primary data using a questionnaire. Respondents in the study were members of the West Sulawesi Regional Police DITPAMOBVIT Police, totaling 45 people, the sample used was the probability sampling technique, and the number of samples was determined using the total sampling method with a sample size of 45 respondents. The formula used in this study, validity test, reliability test, multiple linear regression, t test (partial) and f test (simultaneous). The results in this study indicate that work effectiveness and work efficiency have a partially significant effect on The performance of DITPAMOBVIT West Sulawesi Regional Police and work effectiveness and work efficiency have a significant effect simultaneously on Performance of DITPAMOBVIT West Sulawesi Regional Police. Kata Kunci: Effectiveness Work, Efficiency work and Performance of DITPAMOBVIT West Sulawesi Regional Police.